Abnormal plasticity and drug effect in Parkinson's disease - Enomoto, Hiroyuki; Ugawa, Yoshikazu (Rinsho Shinkeigaku, 2012)
The repetitive transcranial magnetic stimulation (rTMS) has been studied as a method to induce plasticity changes in the human brain. And rTMS is expected as a therapeutic tool for Parkinson's disease, depression, intractable pain and others. We reported a new rTMS protocol, quadripulse stimulation (QPS), is more effective. QPS consists of repeated trains of four monophasic TMS pulses separated by inter-stimulus intervals of 5 ms (QPS-5) and 50 ms (QPS-50), inducing bidirectional motor cortical plasticity in an ISI dependent. QPS-5 leads to the potentiation effect. QPS-50 leads to a depression effect. We investigated the changes of plasticity induced by QPS in patients with Parkinson's disease and the healthy volunteer with oral administration of levodopa. In patients with Parkinson's disease the effect of QPS-5 and QPS-50 was attenuated at Off period. However, when the On period it was recovered. In healthy subjects, effect of QPS was enhanced by levodopa, both QPS-5 and QPS-50.